Impact of pretransplant recipient body mass index on post heart transplant mortality: A systematic review and meta‐analysis. Issue 8 (25th July 2018) - Foroutan, Farid; Doumouras, Barbara S.; Ross, Heather; Alba, Ana C.
Abstract: The ISHLT's 2016 Guidelines on the selection of heart transplant (HT) candidates recommends weight loss prior to listing for persons with body mass (BMI) index greater than 35 kg/m 2 . We conducted a systematic review to assess the impact of BMI on all‐cause mortality. We searched to identify eligible observational studies that followed HT recipients. We used the GRADE system to quantify absolute effects and quality of evidence, and meta‐analyzed survival curves to assess post‐transplant mortality across BMI categories. We found a significantly increased risk of mortality in patients with BMI > 30 kg/m 2 across all age categories, independently of transplant era and study source (BMI 30‐34.9: HR 1.10, 95% CI 1.04‐1.17; BMI ≥ 35: HR 1.24, 95% CI 1.12‐1.38). We also found an increased risk of death in underweight (BMI < 18.5 kg/m 2 ) candidates over 39 years of age (Age 40‐65: HR 1.24, 95% CI 1.02‐1.53; Age > 65: HR 1.70, 95% 1.13‐2.57). We found obesity and underweight BMI to be associated with mortality post‐HT. The similar and overlapping increased risk of mortality in patients with BMI 30‐34.9 and BMI ≥ 35 does not support the recently updated ISHLT guidelines. Future evidence in the form of randomized controlled trials is required to assess effectiveness of interventions targeting obesity‐related comorbidities and weight management.